The Meaning and Function of the Batalam Ampek Tradition from a Cultural Anthropology Perspective in Nagari Tanjung Bonai, West Sumatra - Butiras Falah (Warisan: Journal of History and Cultural Heritage, 2025)
This study explores the meaning and function of the Batalam Ampek tradition as an integral component of the Minangkabau customary marriage ceremony in Nagari Tanjung Bonai, West Sumatra, within the broader context of ongoing social transformation. It seeks to examine how this tradition maintains its relevance and to identify the symbolic, religious, and social functions it performs within the local community. Adopting a qualitative approach, the research collected data through in-depth interviews, participant observation, and a comprehensive literature review. The data were analyzed using a descriptive-interpretative framework to uncover layered meanings and their social significance. The findings demonstrate that Batalam Ampek embodies religious meanings that reflect the integration of adat and Islamic values, symbolic meanings that affirm social structure and kinship roles, and cultural meanings that reinforce collective identity. Functionally, the tradition strengthens social solidarity, preserves interfamily harmony, and facilitates the intergenerational transmission of Minangkabau customary values. The study argues that the continuity of Batalam Ampek transcends its ceremonial dimension, operating as a dynamic socio-cultural mechanism that sustains cohesion and cultural resilience within the local community.